2020
DOI: 10.15421/012020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of indices of metabolism in muscle tissue, liver and gonads of Abramis brama in different periods of the annual cycle

Abstract: The aim of this research was to study the dynamics of metabolism in the body of bream Abramis brama (L.) at different periods of the annual cycle: pre-spawning, spawning, post-spawning and feeding. The object of the study was 55 male and 53 female bream aged 9–13 years, to reduce the effect of age on the studied parameters. Individuals were measured, weighed, gender was determined, gonad maturity stage, age; the condition factor and organ indices were calculated. The content of moisture, dry matter, lipids, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…At the same time, it was shown that with an increase in the growing period, moisture in sturgeon muscles decreases and fat and protein increase (Poleksic et al, 2010;Memis et al, 2011;Kairullaev et al, 2017;Lee et al, 2017). Corresponding age-related changes have been studied in other fish species (Volichenko et al, 2017;Payuta & Flerova, 2020). Timely completion of the process of rearing juveniles in pools will reduce the death of larvae of Russian sturgeon (Sherman et al, 2009;Chebanov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it was shown that with an increase in the growing period, moisture in sturgeon muscles decreases and fat and protein increase (Poleksic et al, 2010;Memis et al, 2011;Kairullaev et al, 2017;Lee et al, 2017). Corresponding age-related changes have been studied in other fish species (Volichenko et al, 2017;Payuta & Flerova, 2020). Timely completion of the process of rearing juveniles in pools will reduce the death of larvae of Russian sturgeon (Sherman et al, 2009;Chebanov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%